Stabilisation of small mono- and bimetallic gold–silver nanoparticles using calix[8]arene derivatives. (18th July 2018) - Ray, Priyanka; Clément, Marie; Martini, Cyril; Abdellah, Ibrahim; Beaunier, Patricia; Rodriguez-Lopez, José-Luis; Huc, Vincent; Remita, Hynd; Lampre, Isabelle
Abstract : We report a facile approach to synthesise small Au–Ag alloyed nanoparticles using a new cali[8]arene derivative as a stabiliser. Abstract : In this paper, we report the synthesis of octa(hydroxy)-octa(mercaptobutoxy)calix[8]arene and its use as a stabiliser of nanoparticles (NPs). We show that the reduction of gold and/or silver ions in the presence of this calix[8]arene in ethanolic solutions leads to the formation of very small spherical nanoparticles (NPs) that are homogeneous in size. Confinement and cooperative effects due to the macrocyclic structure of the calix[8]arenes account for the obtained small sizes and the homogeneity. In the case of the simultaneous reduction of gold and silver ions, STEM-EDX mappings provide evidence of the formation of alloyed Au–Ag NPs stabilised by calix[8]arenes. The surface accessibility and potential catalytic applications of the NPs are tested using the reduction of 4-nitrothiophenol by NaBH4 as a model reaction.